Evaluation of thromboembolic event, basic coagulation parameters, and associated factors in patients with colorectal cancer: a multicenter study - Fitalew Tadele Admasu; Tadesse Asmamaw Dejenie; Gashaw Walle Ayehu; Edget Abebe Zewde; Gashaw Dessie; Dagnew Getnet Adugna; Engidaw Fentahun Enyew; Zeleke Geto; Endeshaw Chekol Abebe (Frontiers in Oncology, 2023)
BackgroundPatients with colorectal cancer are at an increased risk of hemostatic disturbances, and recent studies have shown that coagulation disorders could be the first sign of malignancy. Although coagulopathy is a significant cause of cancer-related death and disability, it is usually underestimated, and there has been no recent scientific evidence regarding the exact burden and its specific determinants. Moreover, the public health importance of the risk of coagulopathy among patients with colorectal polyps has not been addressed.Materials and methodsAn institution-based comparative cross-sectional study was conducted on a total of 500 study participants (250 colorectal cancer patients, 150 colorectal polyp patients, and 100 controls) from January to December 2022. Venous blood was collected for basic coagulation and platelet analysis. Descriptive statistics and non-parametric tests (Kruskal–Wallis and Dunn–Bonferroni pairwise comparisons) were used to compare study parameters among the groups. The test results were expressed as medians and interquartile ranges. Binary logistic regressions were fitted, and statistical significance was declared at a p-value of less than 0.05, with 95% CI.ResultsThe prevalence of coagulopathy among colorectal cancer patients was 198 (79.2%; 95% CI: 73.86, 83.64), while the prevalence was 76 (50.7%; 95% CI: 45.66, 54.34) among colorectal polyp patients. From the final model, age between 61 and 70 (AOR = 3.13: 95% CI: 1.03, 6.94), age > 70 years (AOR = 2.73: 95% CI: 1.08, 4.71), hypertension (AOR = 6.8: 95% CI: 1.07, 14.1), larger tumor size (AOR = 3.31: 95% CI: 1.11, 6.74), metastatic cancer (AOR = 5.8: 95% CI: 1.1, 14.7), and BMI ≥30 kg/m2 (AOR = 3.8: 95% CI: 2.3, 4.8) were positively associated with coagulopathy.ConclusionThis study showed that coagulopathy is a major public health concern among patients with colorectal cancer. Therefore, existing oncology care efforts should be strengthened to prevent coagulopathy among patients with colorectal cancer. Moreover, patients with colorectal polyps should receive more attention.